Start-up financing: How credit ratings and bank concentration impact credit access - Martin Brown; Hans Degryse; Daniel Höwer; MarÍa Fabiana Penas (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Start-ups, especially those in high-tech industries, are an important force for innovation. They contribute to the competitive success of the economy, and help to create new jobs. Bank financing is the most important source of external credit for newly established firms. In the last two decades, bank consolidation and regulatory changes such as Basel II have influenced banks' screening processes, leading to a greater reliance on hard information. Yet newly established firms do not have a financial track record. Publicly available information like credit ratings is rarely available for new firms. Especially in the high-tech sector, a large share of young firms has reported difficulties in obtaining bank loans. For this reason, policy makers are worried that bank consolidation and the increasing reliance of the banking sector on third-party credit ratings may have detrimental effects on the access of start-ups to credit, especially in high-tech industries. This, in turn, could harm the innovative capabilities and competitiveness of German industry. Yet are such worries justified? To answer this question, researchers examined how credit availability is impacted by start-ups' credit ratings as well as the size and industry expertise of their primary bank. The study relied on firm-level survey data from the ZEW/KfW Start-up Panel. – – Externe Kreditwürdigkeitsprüfungen durch Rating-Agenturen haben für Banken bei der Kreditvergabe an Unternehmen, aufgrund der verschärften Regulierung durch Basel II, erheblich an Bedeutung gewonnen. Die These, ungünstige oder fehlende Ratings seien der Grund dafür, dass insbesondere innovative, noch nicht etablierte Unternehmen ohne aussagekräftige Kredithistorie oft erhebliche Schwierigkeiten hätten, Bankkredite zu erhalten, bestätigt sich jedoch nicht. Eine Studie des Zentrums für Europäische Wirtschaftsforschung (ZEW) zeigt zwar, dass negative Ratings generell für Unternehmen den Zugang zu Krediten erschweren. Gerade für junge, innovative Unternehmen fällt dieser Effekt allerdings deutlich geringer aus als für andere.
Keywords: 330